Numerical Simulation of an Improved CZTS/WS2 PV Cell by SCAPS 1-D (GUB Journal of Science and Engineering, 2022)
CZTS solar cells are promising among the third-generation solar cell. Because of its earth abundant materials and less toxicity CZTS solar cell can perform a sustainable role as an absorber layer. The optimization of a buffer layer is still a challenge and efficiency are still low than other thin film solar cells. In this study, WS2 buffer layer have been used to simulate the PV cell structure in SCAPS-1D simulation software. No research has been found where CZTS and WS2 is used together. We have achieved a maximum efficiency of η = 18.90 % at 300 K working temperature and other factors i.e., Voc, Jsc and FF are also promising. The highest certified efficiency of CZTS solar cell is nearly 12%. The simulation profile can be a guideline for fabricating the improved PV cell.GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 8, Dec 2021 P 41-48